Survei Kendala Pelaksanaan Pembelajaran PJOK Materi Pencak Silat SMP Negeri di Kabupaten Semarang (Department of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research is to know the constraints of implemention the learning material physical education pencak silat in Semarang Regency Junior High School 2016. The methode of this research is a descriptive kualitatif. Method of data collection in this study using interview, observation and documentation. The result of the research done indicates that almost all of the Junior High School in Semarang Regency who researched the author indeed there are constraints on the sport of pencak silat to be taught to learners. Obstcales found in giving the subjects of pencak silat at school is the lack of skills and knowledge teachers physical education, the lack of interest of students and the lack of support the head of the school, but the teacher penjas the presence of mteri training wants confides pencak silat which is held by the Departement in order that the teachers can provide such ontent to student. Te conclusion found by the writer is that there are obstacle of the implementation of physical education and sport learning in the material of pencak silat. They are in the aspect of teacher knowledege and skill, the support of the head master, and the minimum student interest.